LIBERAL TRENDS IN THE TATAR PRESS AT THE BEGINNING OF THE 20TH CENTURY - Garnysheva , Tatyana; Khusnutdinova, Rezida (Revista Inclusiones, 2020)
The article is based on a historiographic review of materials on local history. The information contained in periodicals is of exceptional value as a historical source for studying the formation of public opinion in the Russian province at the beginning of the twentieth century. The particular value to the work is given by the authors’ reference to factual material from the provincial Muslim press which testifies for the interaction of the Tatar and Azerbaijani democratic movements in the issues of equal rights of nations within a single state with wide autonomy, in the context of understanding the concepts of “nation” and “national self-determination”. The national periodical press of that period, covering acute and topical issues of all aspects of the socio-political and socio-economic life of the society, was certain to influence the formation of public opinion in the Russian provincial territories.